Laparoscopic Ovarian Cystectomy in A Patient With Vetriculoperitoneal Shunt: a case report - Shrestha, Ranjana; Bhandari, BR; Piya, R; Shrestha, MR (Nepal Journal of Obstetrics and Gynaecology, 2017)
Ventriculoperitoneal shunt (VPS) is often the best treatment modality for neurologic disorders such as hydrocephalus and pseudotumor cerebri. In recent years, laparoscopic surgery has emerged as a preferred method of accessing and treating a variety of abdominopelvic pathology. Laparoscopic procedures were previously contraindicated in patients of hydrocephalus having a Ventriculoperitoneal (VP) shunt due to shunt obstruction, shunt malfunction, infection and acute elevation of intracranial pressure. Now, conclusive evidence indicating that it is safe to perform laparoscopic surgery in a patient with VP shunt using routine anaesthetic monitoring and without any shunt manipulation. We report a case of successfully performing laparoscopic ovarian cystectomy in a patient with VP shunt.